Impella malrotation affects left ventricle unloading in cardiogenic shock patients - Luca Baldetti; Davide Romagnolo; Mariagiulia Festi; Alessandro Beneduce; Davide Gurrieri; Beatrice Peveri; André Frias; Mario Gramegna; Stefania Sacchi; Lorenzo Cianfanelli; Francesco Calvo; Vittorio Pazzanese; et al. (ESC Heart Failure)
Abstract Aims Impella malrotation—inlet orientation away from the left ventricular (LV) apex with normal console waveforms and proper device depth—is commonly observed and possibly associated worse haemodynamics. This study aimed to characterize the haemodynamic consequences of Impella malrotation in cardiogenic shock (CS) patients. Methods and results We included 100 CS patients (60 ± 12 years; 79.0% males) with available echocardiography during Impella support and pulmonary artery catheter assessment before and during (at 48 h) Impella support. Impella malrotation was identified in 36%. At 48 h, malrotation patients had higher pulmonary artery wedge pressure (PAWP, 16.0 ± 8.2 vs. 13.0 ± 4.6 mmHg; P = 0.033), higher systolic pulmonary artery pressure (PAP, 35.0 ± 11.3 vs. 29.5 ± 9.0 mmHg; P = 0.015), higher diastolic‐PAP (19.3 ± 8.1 vs. 15.1 ± 6.1 mmHg; P = 0.007), higher mean‐PAP (25.7 ± 9.1 vs. 20.8 ± 6.8 mmHg; P = 0.005), higher right atrial pressure (10.3 ± 4.8 vs. 7.7 ± 4.3 mmHg; P = 0.009), higher pulmonary vascular resistance index (4.78 ± 2.75 vs. 3.49 ± 1.94 WUm2; P = 0.020) and higher pulmonary artery elastance (0.91 ± 0.60 vs. 0.67 ± 0.40 mmHg/mL; P = 0.045). Serum lactate at 48 h was higher in malrotation patients (6.63 ± 6.25 vs. 3.60 ± 4.21 mmol/L; P = 0.004). Malrotation patients presented larger LVEDD during support (52 ± 10 vs. 46 ± 11 mm; P = 0.006), higher rates of aortic regurgitation (AR, 86 vs. 56%; P = 0.004) and higher increase in AR severity (+0.94 ± 0.92 vs. + 0.46 ± 0.95; P = 0.016). No significant differences were found in major adverse outcomes. Conclusions In CS patients, Impella malrotation is associated with suboptimal unloading of the LV, worse pulmonary haemodynamics and worse indexes of right ventricular afterload.